Controlled release from protein particles encapsulated by molecular layer deposition. Issue 63 (14th August 2015) - Vasudevan, Siddarth A.; Xu, Yaolin; Karwal, Saurabh; van Ostaay, Helena G. M. E.; Meesters, Gabriel M. H.; Talebi, Mojgan; Sudhölter, Ernst J. R.; Ruud van Ommen, J.
<x xml:space="preserve">Abstract</x> Molecular layer deposition was applied for coating micron-sized protein particles to control their dissolution behaviour.